A Lei 10.639/03 e as políticas educacionais : debates e tendências - Sberse, Anete Julia Kornowski (2012)
The current essay presents a study about the context in which the process of development and implementation of the law 10.639/03, which made mandatory the teaching of Afro-Brazilian History and Culture in the official curriculum of the school system. Since this law is being implemented in schools, the experiences and reflections already done, seen and practiced during this time after its promulgation and the challenges and perspectives in terms of its fulfillment, particularly of those directly involved in the places where the law is being practiced, serve us for analysis and reflection so that it may be implemented with success and reach the objectives it aims for. To accomplish that, we used the questions discussed in masters degree dissertations and thesis that focused on the theme of racial relations developed in pos-graduation programs having as basis the Theses Database of the Superior Degree Personnel Improvement Coordination (CAPES). The role and contribution of the Black Movement in the achievement of the law also are analyzed and highlighted here. Being an active and participative social movement striving for human rights and for the fulfillment of its obligation and by exercising citizenship, they fulfill an important role in building a multicultural, just and human society, that learns, respects, values and knows how to live with the difference. The school, as the place of socialization of knowledge, can t ignore its role visà-vis the knowledge and the contribution of this history and culture, that also takes part in the construction of our society and of the peoples that constitute Brazil, contributing to the formation of a new mentality, geared towards the overcoming of all forms of discrimination and exclusion